Multi-source all-solid-waste low-carbon cementing material with high silicon-calcium ratio

By screening and combining solid waste from different industries, a multi-source all-solid waste low-carbon gelling material with high silicon-calcium ratio was prepared, which solved the problems of high gelling materials cost and low resource utilization efficiency in tailings filling technology, and achieved low-cost and environmentally friendly filling performance.

CN119822657APending Publication Date: 2025-04-15CHINA UNIV OF GEOSCIENCES (BEIJING) +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510033896.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the existing tailings filling technology, gelling materials are costly and have serious environmental pollution. They fail to effectively utilize the high content of silica in tailings, resulting in low resource utilization benefits.

Method used

By screening solid waste from different industries, adjusting the group distribution ratio, a multi-source all-solid waste low-carbon gelling material with high silicon-calcium ratio is prepared, and materials such as steel slag powder, slag powder, calcium carbide slag powder and gypsum powder are used to form a high-strength filler through hydration reaction.

Benefits of technology

It realizes low-cost and environmentally friendly production of gelled materials, reduces carbon emissions and energy consumption during the production process, improves tailings resource utilization rate, and meets the filling performance requirements of silicon-containing tailings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a multi-source all-solid-waste low-carbon cementing material with a high silicon-calcium ratio. The cementing material comprises the following raw material components in percentage by mass when the sum of the raw material components is 100%: 20-30% of steel slag powder, 50-60% of slag powder and 15-20% of composite powder, the composite powder is prepared by mixing carbide slag powder and gypsum powder according to a mass ratio of 3: (0.9-1.2). The low-carbon cementing material is prepared from industrial solid wastes such as slag, steel slag, carbide slag and gypsum, and silicon of the silicon-containing tailings participates in the hydration process of the cementing material, so that resource utilization of the solid wastes is realized; when the cementing material disclosed by the invention is used for cementing the iron tailings and the copper tailings, the 28-day compressive strength can reach 2.5 MPa, and the filling strength completely meets the performance requirement of mine filling. The cementing material provided by the invention is simple in preparation process, low in cost, wide in raw material source, and more energy-saving and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cementitious materials for filling tailings in underground mining mines, and specifically relates to a full-solid waste cementitious material with a high silicon-calcium ratio. The present invention can be widely used in underground mines mined by the tailings filling method, and is particularly suitable for underground cementitious filling of tailings with a silicon dioxide content of more than 20%. The present invention can also be used as a low-strength fluid filling material for pipeline cushions, low-grade road subbases, and the like. Background Art

[0002] The promotion and application of underground mine tailings filling mining technology has effectively promoted the disposal of surface tailings. However, tailings are used as aggregates in filling technology, and cement and other alkali-activated materials are used as cementing materials, most of which have high costs or are unfavorable to the environment. For example, the Chinese patent (CN201510166877) uses slag, fly ash, cement clinker, lime, and gypsum in proportion to prepare a new type of binder for tailings consolidation and discharge, which can meet the filling performance requirements, but the raw material cost of this method is relatively high. For ordinary tailings-based cementitious materials, since the activity of the tailings themselves is very low, high-temperature thermal activation or chemical agent treatment is usually required to make cementitious materials, resulting in high costs and difficulty in industrialization.

[0003] Research shows that tailings can be used to develop cementitious materials for underground filling. For example, in Chinese patent CN2020107722659, the tailings are dried and then subjected to mechanical ball milling activation treatment, thermal activation treatment, and chemical agent activation treatment to obtain tailings-based cementitious materials. This material has good filling performance, but its thermal activation process requires a high temperature of 300 to 1000°C, so it also has the problems of high energy consumption and environmental pollution.

[0004] At present, most of the ore tailings that need to be disposed of in my country have a large proportion of medium-silicate gangue minerals, and the SiO2 content is usually higher than 50%, and SiO2 is an extremely important reaction precursor for hydration reactions. The calcium-silicon ratio of cement is about 1.8. When used to treat high-silicon tailings, the calcium-silicon ratio inside the cement body drops significantly, which is not conducive to the hydration reaction inside the slurry. Considering the utilization of SiO2 in tailings, the calcium-silicon ratio of the slurry after mixing with the cementitious material should tend to the normal calcium-silicon ratio of the cementitious material. Therefore, the use of a combination of multi-source solid waste to prepare high-calcium-silicon ratio cementitious materials is a new concept and technology with very broad application prospects. Previous studies mostly focused on the extraction of silicon from tailings, but the extracted products were limited by the scope of application and cost, and the industrialization process was hindered. In addition, there is little research on the full utilization of silicon in tailings in tailings filling technology, and there are basically no related patents published.

[0005] Since the all-solid waste-based low-carbon cementitious materials use solid waste from industries such as steel, agriculture, forestry, coal and electricity, they have a certain activity without high-temperature roasting again, and can effectively reduce carbon emissions in the production process of cementitious materials. Any combination of multiple solid wastes can be used to design high-silicon-calcium ratio cementitious materials that meet the filling performance for the filling and disposal of silicon-containing tailings. Based on the above considerations, the present invention screens solid waste from different industries and adjusts the component ratio to prepare a new type of cementitious material for mine filling, which not only realizes the resource utilization of silicon-containing tailings, but also reduces the production cost of cementitious materials. Summary of the invention

[0006] The purpose of the present invention is to provide a multi-source all-solid waste low-carbon cementitious material with low raw material cost, wide sources, simple preparation process and high silicon-calcium ratio, so as to solve the technical problems of high cost of cementitious materials, large output of untreated silicon-containing tailings, difficult disposal and low efficiency of tailings resource utilization in the existing tailings filling technology, so as to effectively solve the problems of high carbon emission and energy consumption caused by complex process in solid waste treatment and material preparation.

[0007] To achieve the above-mentioned purpose of the present invention, the present invention provides a multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio. The mass content of each component when the sum of the raw material components is 100% is: 20% to 30% steel slag powder, 50% to 60% slag powder, and 15% to 20% composite powder; the composite powder is prepared by mixing calcium carbide slag powder and gypsum powder in a mass ratio of 3: (0.9 to 1.2).

[0008] Preferably, the steel slag powder is crushed and ground to a powder with a particle size of less than 62 μm accounting for more than 90% by mass, a CaO content of not less than 45wt%, a SiO2 content of not less than 11wt%, and a Fe2O3 content of not less than 25wt%.

[0009] Preferably, the slag powder is of S95 grade, and the fineness after grinding is less than 35 μm, with a particle size of more than 90% by mass, a CaO content of not less than 44wt%, a SiO2 content of not less than 25wt%, and an Al2O3 content of not less than 13.5wt%.

[0010] Preferably, the calcium sulfate content in the gypsum powder is greater than 97%, and the powder with a particle size of less than 22 μm accounts for more than 90% by mass.

[0011] Preferably, the carbide slag powder is dried and ground to a powder with a particle size of less than 9 μm accounting for more than 90% by weight, a CaO content of not less than 97wt%, and a SiO2 content of not less than 0.5wt%.

[0012] Preferably, the composite powder is prepared by mixing carbide slag powder and gypsum powder in a mass ratio of 3:1. The composite powder is a mixture of the Ca component and OH in the high calcium system.- and SO4 2- main donor.

[0013] Preferably, the cementitious material is prepared by uniformly mixing steel slag powder, slag powder, carbide slag powder and gypsum powder in proportion.

[0014] The technical principle of the multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio of the present invention is that after the cementitious material reacts with water, the calcium-rich carbide slag powder and gypsum powder in the composite powder significantly increase the Ca content of the material, thereby facilitating the formation of high calcium conditions. 2+ The concentration of Ca in the solution gradually increases as the hydration reaction proceeds. 2+ Charge-balancing OH - The ion concentration decreases, and the charge balance of the anion reduction is balanced by the silicate (aluminate) ion group. During this period, the dissolution rate of the silicate (aluminate) particle surface in steel slag, slag and silicon-containing tailings increases rapidly. In the hydration reaction, the calcium carbide slag powder releases hydroxide ions (OH - ), gypsum powder provides sulfate ions (SO4 2- ), the two together promote the hydration reaction and enhance the hardening effect of the material. Under the joint stimulation of gypsum and carbide slag, the soluble Si (Al) in the slag and tailings reacts with the Ca in the system. 2+ Hydration products such as hydrated calcium silicate gel, hydrated calcium silicate gel and ettringite are formed. Fe-Ca oxides in steel slag will promote the formation of calcium ferrite gel, thereby greatly improving the strength of the filling body. In the later stage of the reaction, the pH continues to rise, and the hydration products wrap the slag particles and tailings particles, which greatly reduces the speed of providing Si (Al) dissolved substances, thereby reducing the generation rate of hydration products and OH - The speed of being consumed. Under the condition of ensuring effective strength, the hydration products do not grow excessively, which leads to cracking and damage of the filling specimen. Therefore, the high silicon-calcium ratio all-solid waste low-carbon cementitious material can be used as the cementitious material for silicon-containing tailings filling.

[0015] Experimental studies have shown that the multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio prepared by the present invention is particularly suitable for underground cementing and filling of iron-containing tailings with a silicon dioxide content of 20% to 50%.

[0016] Compared with the prior art, the multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio of the present invention has the following advantages:

[0017] (1) The silicon-calcium-based solid waste used in the multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio prepared by the present invention is a common waste and by-product in the smelting industry, coal power industry, steel industry and chemical industry, and has a wide range of sources. By rationally regulating the content of the components, a high-application-value material for the disposal of silicon-containing tailings is prepared, thereby improving the resource utilization rate of solid waste and reducing solid waste accumulation pollution. Through appropriate industrial technology, the synergistic hydration mechanism between solid wastes is utilized to promote the complementary advantages between solid waste materials, thereby improving the development and utilization of low-carbon cementitious materials with solid wastes mainly composed of silicon and calcium as raw materials.

[0018] (2) The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio prepared by the present invention has a component ratio that can be controlled according to the silicon content of the tailings, which can effectively give the slurry good coagulation characteristics and mechanical properties. The 28-day strength of the cementitious material is greater than 20MPa, and can be directly used as a low-strength fluid filling material such as backfill in mine goafs, pipeline cushions, and low-grade road subbases.

[0019] (3) The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio produced by the present invention is inexpensive: the materials used in the present invention are all solid waste and do not require secondary calcination. The production process is simple, environmentally friendly, and requires low investment, which reduces the carbon emissions and energy consumption of the calcination of traditional cementitious material clinkers.

[0020] (5) The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio prepared by the present invention has a cost that is more than 40% lower than that of ordinary Portland cement, has strong market competitiveness, and has good economic and environmental benefits. DETAILED DESCRIPTION

[0021] To describe the present invention, a multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio according to the present invention is further described in detail below in conjunction with embodiments.

[0022] In the embodiment, converter slag from a domestic steel plant is used to prepare the mixed material after grinding. The slag powder is taken from the water-quenched blast furnace slag of the same steel plant. The selected material composition is shown in Table 1:

[0023] Table 1 Raw material composition

[0024]

[0025] In the embodiment, a multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio is prepared by the following steps:

[0026] (1) After the steel slag is naturally dried, it is crushed into small pieces less than 3 mm by a crusher, and then ground into steel slag powder with a fineness of 62 μm accounting for more than 90% by a ball mill for standby use.

[0027] (2) Slag powder, steel slag powder, and composite powder (carbide slag: gypsum = 3:1) are mixed according to the ratios shown in Table 2 to obtain three composite powders with different ratios for standby use. The ratios in the embodiment are shown in Table 2:

[0028] Table 2 Proportions of multi-source all-solid waste low-carbon cementitious materials with high silicon-calcium ratio prepared by the present invention

[0029]

[0030] The proportion of the mine tailings filling slurry in the embodiment is shown in Table 3:

[0031] Table 3 Proportions of mine filling slurry prepared by the present invention

[0032]

[0033]

[0034] The mine tailings used in the embodiment were iron tailings and copper tailings from different mines in China for cementation test. The main mineral components of the tailings are shown in Table 4:

[0035] Table 4 Main mineral composition of tailings

[0036]

[0037] Prepare a filling slurry with a mass concentration of 68% according to Table 3. Use a Φ50×100mm cylindrical mold, place it in a standard cement curing box for curing (temperature 20±2℃, humidity 90±2%) after casting, demold it after 24 hours, continue curing, and test the uniaxial compressive strength at different ages. Use a DYE-2000 electro-hydraulic press to test the uniaxial compressive strength of the test piece at different curing ages, and the test results are shown in Table 5.

[0038] Table 5 Iron tailings and copper tailings cemented filling strength

[0039]

[0040]

[0041] The experiments in the examples show that the three cementitious materials with different proportions prepared by the present invention are used to carry out cementing filling tests on iron tailings and copper tailings. The experimental results show that they all meet the filling performance requirements of 2-day compressive strength ≥ 0.5MP, 7-day compressive strength ≥ 1.0MP, and 28-day compressive strength ≥ 2.5MP, and the cost is only 43% of that of cement as the filling cementitious material.

Claims

1. A multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio, characterized in that The mass content of each component when the sum of the raw material components is 100% is: 20% to 30% of steel slag powder, 50% to 60% of slag powder, and 15% to 20% of composite powder; the composite powder is prepared by mixing carbide slag powder and gypsum powder in a mass ratio of 3: (0.9 to 1.2).

2. The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio as claimed in claim 1, characterized in that: The steel slag powder is crushed and ground to a powder with a particle size of less than 62 μm accounting for more than 90% by weight, a CaO content of not less than 45wt%, a SiO2 content of not less than 11wt%, and a Fe2O3 content of not less than 25wt%.

3. The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio as claimed in claim 1, characterized in that: The slag powder is of S95 grade, and after grinding, the fineness is less than 35 μm, with the particle size accounting for more than 90% by mass, the CaO content is not less than 44wt%, the SiO2 content is not less than 25wt%, and the Al2O3 content is not less than 13.5wt%.

4. The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio as claimed in claim 1, characterized in that: The calcium sulfate content in the gypsum powder is greater than 97%, and the powder with a particle size of less than 22 μm accounts for more than 90% of the mass.

5. The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio as claimed in claim 1, characterized in that: The carbide slag powder is dried and ground to a powder with a particle size of less than 9 μm accounting for more than 90% by weight, a CaO content of not less than 97wt%, and a SiO2 content of not less than 0.5wt%.

6. The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio as claimed in claim 1, characterized in that: The composite powder is mixed in a mass ratio of carbide slag powder to gypsum powder of 3:

1.

7. The multi-source all-solid waste low-carbon cementitious material with a high silicon-calcium ratio as claimed in claim 1, 2, 3, 4, 5 or 6, characterized in that: Mix steel slag powder, slag powder, carbide slag powder and gypsum powder in proportion and evenly configure them.

Citation Information

Patent Citations

  • A method for preparing a tailings consolidation and discharge binder

    CN104817286B